Understanding the relationship between children's oral health utilization and parent's use of healthcare services - Naavaal, Shillpa; Lamsal, Rashmi (Frontiers in Oral Health, 2025)
IntroductionParents play an influential role in their children's lives, but little is known about how their healthcare experiences connect. This study examined the relationship between parent's healthcare use and their child's overall and preventive dental care use.MethodsWe pooled three years (2017–2019) of Medical Expenditure Panel Survey (MEPS) data and merged child (0–17 years) and parent data. Our outcomes included any dental visit, preventive visit, and receipt of sealant or fluoride. The primary exposure variable was the parents’ medical and dental care use, grouped into four categories. Descriptive and bivariate analyses were conducted, and multivariable logistic regression analyses were used to examine the associations.ResultsThe study included data from 9,927 children. Overall, 50.1%, 42.3%, and 21.2% had any dental visit, preventive visit, and fluoride or sealant application, respectively, in the past 12 months. Among parents, 38.3% had both medical and dental visits, 5.8% had a dental but no medical, 36.7% had a medical but no dental, and 19.1% had neither. Children whose parents had medical and dental visits had more than five times the odds of having any dental visit (aOR = 5.49, 95% CI: 4.64, 6.52) and preventive dental visit (aOR = 5.41, 95% CI: 4.57, 6.39) and 3.64 times the odds of receiving sealant or fluoride application (95% CI: 2.93, 4.53) compared to those whose parents had no dental and medical visits.ConclusionsChildren's oral health utilization is strongly linked with parents’ healthcare use. It can be improved by educating parents and supporting their healthcare use.